To solve the equation \(3x^2 - 5x = -6\), we first rearrange it into standard quadratic form:
\[ 3x^2 - 5x + 6 = 0 \]
Next, we can apply the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
where \(a = 3\), \(b = -5\), and \(c = 6\). First, we calculate the discriminant \(b^2 - 4ac\):
\[ b^2 = (-5)^2 = 25 \] \[ 4ac = 4 \cdot 3 \cdot 6 = 72 \] \[ b^2 - 4ac = 25 - 72 = -47 \]
Since the discriminant is negative, the solutions will involve imaginary numbers. We can now substitute back into the quadratic formula:
\[ x = \frac{-(-5) \pm \sqrt{-47}}{2 \cdot 3} = \frac{5 \pm \sqrt{-47}}{6} \]
This can be simplified to:
\[ x = \frac{5}{6} \pm \frac{i \sqrt{47}}{6} \]
Thus, the conjugate pair of solutions is:
\[ \frac{5}{6} \pm \frac{i \sqrt{47}}{6} \]
Looking at the given options, the correct choice matching our solutions is:
\[ \frac{5}{6} \pm \frac{i \sqrt{47}}{6} \]
Therefore, Djamila should choose:
−56±i47√6.